Book Reviews. Issue 1 (1st January 2016) - Lucamante, Stefania; Formica, Serena; Valente, Donatella; Bini, Andrea; d'Arcangeli, Luciana
Sardinia on the Screen: The Construction of the Sardinian Character in Italian Cinema, Maria Bonaria Urban (2013) Amsterdam: Rodopi (Studia Imagologica), 579 pp., ISBN: 9789042037502, h/bk 149.69The Mirage of America in Contemporary Italian Literature and Film, Barbara Alfano (2013) Toronto: Toronto University Press, 190 pp., ISBN: 9781442644052, p/bk, £36.20PIERRE SORLIN. MEMORIA NARRAZIONE AUDIOVISIVO, SILVIA LEONZI (ED.) (2013) Roma: Armando Editore, 143 pp., ISBN: 9788866773474, p/bk, 10.00Commedia nell'Italia contemporanea, I. A. De Pascalis (2012) Milan: Il Castoro, 175 pp., ISBN: 9788880336167, p/bk, 13.18Zoom d'oltreoceano: Is tantanee sui registi italiani e sull'Italia, Daniela De Pau and Simone Dub rovic (eds ) (2010) Manziana, Rome: Vecchiarelli Editore, 351 pp., ISBN: 9788882472719, p/bk, 30.00